Environmentally safe corrosion inhibitor: evaluating extracts of Plectranthus barbatus Andrews (Research, Society and Development, 2018)
The work presents an evaluation of the ethanolic and aqueous extracts of Plectranthus barbatus Andrews (Brazilian boldo) as potential natural corrosion inhibitors for P110 carbon steel and 22Cr-7Ni-3Mo stainless steel (duplex 22 %Cr) in a medium containing hydrochloric acid 1,0 mol.L-1 and sulfuric acid 0,5 mol.L-1. The study was carried out under of gravimetric tests with variation in the concentration of extracts and attainment inhibition efficiency, and by analyzing the chemistry profile to identify metabolites present in the extracts. The results indicated the absence of terpenes and the presence of flavonoids, tannins and phenolic compounds in both extracts. The gravimetric tests showed that the extracts present excellent results for carbon steel in both acids with inhibition efficiency values higher than 90 %, indicating the potential of the extracts as corrosion inhibitors for carbon steel. However, they do not present for stainless steel the same performance, revealing low inhibition efficiency values not justifying the use of the extracts as inhibitors for this steel. The aqueous and ethanolic extracts have different behaviors according to the acid used, with the ethanolic giving better results in sulfuric acid and aqueous extract in hydrochloric acid.